A study on healthcare utilization for actinic keratoses in the Netherlands highlights a global issue. (1st September 2019) - Misitzis, A.; Beatson, M.; Weinstock, M.A.
Abstract: Linked Article : Noels et al . Br J Dermatol 2019; 181 :544–553 .